The Role of Flip Charts in Improving English Vocabulary Acquisition - Nur Hayati; Hidayah Nor (UMBanjarmasin, 2023)
Students' motivation and interest in what they are learning can both be increased with the use of educational media. There is a wide range of media kinds that are utilized in the learning process, from basic to advanced. One basic sort of media is flip chart media. This study intends to ascertain how flip chart media is used in English vocabulary instruction and what tutors think about it. The participant in this study was a tutor who worked with Class Group 21 of UPB (Unit Pengembangan Bahasa) at the Islamic State University of Antasari Banjarmasin. In this study, data were gathered through interviews and observation using a descriptive qualitative methodology. According to the research findings, flip chart media can improve students' motivation and comprehension while also aiding in vocabulary learning. The findings indicate numerous crucial processes involved in using flip charts to aid in vocabulary development. The following strategies are used by the tutor: 1) self-preparation; 2) appropriate flip chart placement; 3) seating arrangement of students; 4) material introduction and informational picture and text presentation understandably and straightforwardly; 5) tutor makes sure every student can see the flip chart clearly; and 6) instructs students to form a semicircle or U position. Because of its adaptability and capacity to support more engaging and innovative instruction, the tutor also held a favorable opinion of the usage of this media. This study serves as a valuable resource for further research in the same field and significantly enhances the quality of vocabulary instruction in English.